DEVELOPMENT OF PHYSICS LEARNING MODEL TO IMPROVE SCIENTIFIC CHARACTERS OF JUNIOR HIGH SCHOOL STUDENT - Martawijaya, Muhammad Agus (Journal of Educational Science and Technology, 2015)
ABSTRACTIndonesia is experiencing a crisis that led to the occurrence of horizontal conflicts among its citizens. This crisis is an indication that the characters of Indonesian people has declined and deviated from the appreciation and the practice of Pancasilaâs values as a foundation of the Republic of Indonesia (RI). To overcome this problem, a valid, practical, and effective learning model was developed by integrating the local wisdom as a cultural element into a learning process to enhance the scientific characters of students, especially scientific honesty. Aâbulo sibatang is one of the local wisdom that is integrated into the developed learning model. Following the expert validation process, the learning model was tested on a limited basis and the model was considered valid. Based on the trial on limited basis, it was found that the learning physics model that integrated with the local wisdom met the criteria of validity and practicality, and was found to increase the scientific honesty of students effectively. This model can be applied to other places in accordance with the characteristics of the study site, the subject of research, and the educators who will become educatorâs model.